THE BENEFITS OF AN ENVIRONMENTAL MANAGEMENT SYSTEM (EMS) AND REGISTRATION OF THE EMS TO ISO 14000 AND FUNDAMENTALS OF QUALITY MANAGEMENT SYSTEM BY ISO 9000 - Dr. S. Rajyalakshmi; Dr. K. Samuel Kumar; R. Jayashree; Dr. V. Tejeswara Rao (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
An ISO certification attests to the fact that a manufacturing process, documentation technique, service, or management system satisfies all standardization and quality assurance requirements. The International Organization for Standardization, or ISO, is a global non-governmental organization that operates independently and creates standards to guarantee the effectiveness, safety, and quality of systems, goods, and services. There are ISO certifications in numerous industries, ranging from medical devices and energy management to social responsibility and energy management. The purpose of ISO standards is to guarantee uniformity. Every certification has its own set of requirements and is categorized numerically.